DNA molecular markers in plant breeding: current status and recent advancements in genomic selection and genome editing. Issue 2 (4th March 2018) - Nadeem, Muhammad Azhar; Nawaz, Muhammad Amjad; Shahid, Muhammad Qasim; Doğan, Yıldız; Comertpay, Gonul; Yıldız, Mehtap; Hatipoğlu, Rüştü; Ahmad, Fiaz; Alsaleh, Ahmad; Labhane, Nitin; Özkan, Hakan; Chung, Gyuhwa; et al.
ABSTRACT: With the development of molecular marker technology in the 1980s, the fate of plant breeding has changed. Different types of molecular markers have been developed and advancement in sequencing technologies has geared crop improvement. To explore the knowledge about molecular markers, several reviews have been published in the last three decades; however, all these reviews were meant for researchers with advanced knowledge of molecular genetics. This review is intended to be a synopsis of recent developments in molecular markers and their applications in plant breeding and is devoted to early researchers with a little or no knowledge of molecular markers. The progress made in molecular plant breeding, genetics, genomic selection and genome editing has contributed to a more comprehensive understanding of molecular markers and provided deeper insights into the diversity available for crops and greatly complemented breeding stratagems. Genotyping-by-sequencing and association mapping based on next-generation sequencing technologies have facilitated the identification of novel genetic markers for complex and unstructured populations. Altogether, the history, the types of markers, their application in plant sciences and breeding, and some recent advancements in genomic selection and genome editing are discussed.